Teddy Robinson stories - Robinson, Joan G. 1910-1988 (Kingfisher, 2002)
Teddy Robinson is a big, comfortable teddy bear who belongs to a little girl called Deborah. He is sometimes shy, and sometimes a bit of a show-off, but always ready to make the best of things, whether he is spending the night in hospital or playing pirates at the seaside
Keywords: Robinson, Teddy (Fictitious character) / Juvenile fiction; Teddy bears / Juvenile fiction; Children's stories, English; Robinson, Teddy (Fictitious character); Teddy bears; Fiction; Juvenile works; Children's nonfiction; Children's fiction